Degree of resistance of hetero- and homozygous resistant genotypes of a target-site resistant blackgrass biotype (haplotype Leu1781) in dose-response experiments with clethodim and cycloxydim - Wagner, Jean; Belz, Regina G. (Julius-Kühn-Archiv, 2014)
In dose-response experiments and by molecular analyses the reaction of a black grass biotype (Alopecurus myosuroides) with target site resistance to ACCase inhibitors (Ile1781-Leu) was examined for the response to clethodim and cycloxydim and compared to the responses of the homozygous and heterozygous subpopulations. To decipher the population into the homo- and heterozygous sub-populations, individual plants of the resistant biotype were analyzed for the haplotype Leu1781 by means of SNP analytics (pyrosequencing). For the entire population, significant different resistance factors (RF) of 8 and 153 resulted for clethodim and cycloxydim, respectively. For the heterozygous sub-population a RF of 6 was estimated for clethodim and 118 for cycloxydim. For the homozygous sub-population a RF of 10 for clethodim and 136 for cycloxydim was estimated. The RF between the homo- and heterozygous sub-populations for each herbicide were, however, not significantly different. Despite this, a tendency of the heterozygous sub-population being less resistant was indicated. Therefore, it is hypothesized that the selection of resistance depends not only on the herbicide used, but on the frequency of the genotypes in a field population. Furthermore, the significant different reaction of black grass with the haplotype 1781 to both tested herbicides reflects the meaning of the individual constellation of active ingredient, resistance mechanisms and genotype for selection and spread of resistance.